Facet deformation minimizing fresnel lens die roller and manufacturing method (2014)
A die roller and method for making a die roller for use in manufacturing Fresnel lens angular segments or sub-segments, the die roller having one or more segment dies and curvilinear Fresnel facet dies, the Fresnel facet dies having a collar, a peak, and a base, the collar being sloped, the peak being rounded, and the base being rounded, according to a die algorithm based upon one or more facet factors, in order to reduce the deformation of Fresnel lens angular segments or sub-segments extruded with the die roller.